2013
DOI: 10.1186/2193-1801-2-425
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Enterococci indicator for bacteriological quality monitoring of beaches in Malaysia using a multivariate approach

Abstract: There is currently no established bacteriological beach quality monitoring (BQM) program in place in Malaysia. To initiate cost-effective, sustainable bacteriological BQM schemes for the ultimate goal of protecting public health, policy decision makers need to be provided robust, indigenous empirical findings that validate appropriate water quality parameters for inclusion in such monitoring programs. This is the first study that assesses the validity of enterococci as an ideal indicator for bacteriological BQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This indicates that recreational water quality is regularly threatened by both enteric and non-enteric heterotrophic bacterial species. These organisms have been widely reported for their public health importance [28][29], as they cause different disease conditions in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that recreational water quality is regularly threatened by both enteric and non-enteric heterotrophic bacterial species. These organisms have been widely reported for their public health importance [28][29], as they cause different disease conditions in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the occurrence of potentially pathogenic Enterococcus spp., Aeromonas spp . Staphylococcus spp ., Pseudomonas spp ., Viruses , Salmonella, campylobacter , and E. coli , isolated either from beach sand, seawater or in both samples (Elmanama et al., 2005; Curiel-Ayala et al., 2012; Ahmad et al., 2013). Sewage pollution causes more threats to recreational water users than animal faecal contamination (Soller et al., 2010), making it important to detect their sources in recreational water so that proper mitigation approaches can be put into practice, and hazards precisely measured.…”
Section: Introductionmentioning
confidence: 99%